Manure pathogens [ manure management, regulations, and water quality protection - Bowman, wight D. (Water Environment Federation Press;New York : McGraw-Hil, 2009)
Addressing the concern about how pathogens present in animal manure effect human health, this work covers what these pathogens are, how they can be managed properly, and regulations